The analysis of discriminant factors related to team match performances in the 2012 European Football Championship - Sgro, F.; Barresi, M.; Lipoma, M. (Journal of Physical Education and Sport, 2015)
The aim of this work was to identify the indicators related to team match performances (i.e., the scoring opportunities and offensive and defensive strategies) that could discriminate beteen winning or losing teams in the matches played in the 2012 European Football Championship. In order to achieve such an objective, we have analyzed the matches did not end in a draw within the regulation time by means of the notational analysis approach. The one-way analysis of the performance indicators revealed that the scoring opportunities (i.e., goals, number of shots, and effectiveness) and the number of assists were the significant differing indicators between the winning and losing teams. The discriminant analysis returned a cross-validated model with a classification accuracy of about 80%. Goals and assists were the discriminants that are most significant for the explanation of the match`s result. This work provides specific technical and tactical insights that may be useful for coaches and trainers in the preparation of high-level and short-duration competitions.